Serum miR-29a Is Upregulated in Acute Graft-versus-Host Disease and Activates Dendritic Cells through TLR Binding - Ranganathan, Parvathi; Ngankeu, Apollinaire; Zitzer, Nina C; Leoncini, PierPaolo; Yu, Xueyan; Casadei, Lucia; Challagundla, Kishore; Reichenbach, Dawn K; Garman, Sabrina; Ruppert, Amy S; Volinia, Stefano; Hofstetter, Jessica; et al. (The Journal of immunology (1950), 2017)
Acute graft-versus-host disease (aGVHD) continues to be a frequent and devastating complication of allogeneic hematopoietic stem cell transplantation (HSCT), posing as a significant barrier against the widespread use of HSCTs as a curative modality. Recent studies suggested serum/plasma microRNAs (miRs) may predict aGVHD onset. However, little is known about the functional role of circulating miRs in aGVHD. In this article, we show in two independent cohorts that miR-29a expression is significantly upregulated in the serum of allogeneic HSCT patients at aGVHD onset compared with non-aGVHD patients. Serum miR-29a is also elevated as early as 2 wk before time of diagnosis of aGVHD compared with time-matched control subjects. We demonstrate novel functional significance of serum miR-29a by showing that miR-29a binds and activates dendritic cells via TLR7 and TLR8, resulting in the activation of the NF-κB pathway and secretion of proinflammatory cytokines TNF-α and IL-6. Treatment with locked nucleic acid anti–miR-29a significantly improved survival in a mouse model of aGVHD while retaining graft-versus-leukemia effects, unveiling a novel therapeutic target in aGVHD treatment or prevention.